Efektifitas Dan Perencanaan Investasi Sektoral Dengan Menggunakan Metode Incremental Capital Output Ratio (Studi Kasus Sektor-Sektor Perekonomian Kota Tarakan) - Basran, Zakaria (Ekonomika, 2010)
This  study aims to determine the economic development and investment in the city of Tarakan, knowing the effectiveness of investment in every sector of the economy Tarakan City, and to perform acts of investment planning at every economic  sector basedon economic growth target is expected. Research location in the City of Tarakan, with 2-month study, which  analyzed the data using data obtained from  BPS Tarakan City, Bank Indonesia Samarinda, with the studied time period from 2004 to 2007. Analysis using ICOR (Incremental Output Ratio). Then proceed with the analysis models for investment planning based on economic growth target in the desired 9 main sectors in the City of Tarakan. The results showed that, in a sectoral, economic sector, the least effective in the utilizationof investment is the building sector with a value of 12.996. Meanwhile,according to the study period, the year 2006 was the period of the lowest effective level of 8.475. Based on the average value of ICOR Economy of Tarakan City is at the level of investment effectiveness is 6.177 normal, because its economic structure is dominated by services that require more investment. Determination of the economic growth target of 8,5% per year 2009-2012 need increased funding expect mining sector, since this sector based on the results of ICOR analysis showed a negative value which means that the trend growth declined while funding for these investments continue to rise. Key Words: Investment, Economic Sector, Effectiveness, ICOR